Juvenile crime and justice - Chambliss, William J. (Key issues in crime and punishment, 2011)
Presents arguments both in favor of and opposed to various treatments, programs, and punishments, examining issues such as youth curfews, juveniles in adult courts, legal representation for juveniles, juvenile boot camps, group homes, and out-of-home placement.